Regional integration as a factor of increasing national competitive ability - N U Sopilko (RUDN Journal of Economics, 2012)
The author formulated a concept of a regional competitive ability - national economies integration influences regional competitive ability positively, that provides additional competitive advantages. It was found out that there are tendencies of Russian and Ukrainian cooperation strengthening in the CIS and regional integration can provide a long - term competitive ability on the basis of neighborhood effect with an optimal combination of all regional factors.